ANALISIS PENGARUH TATA KELOLA PERUSAHAAN YANG BAIK TERHADAP RASIO PEMBAYARAN DIVIDEN - Eko Budi Santoso (Jurnal Riset Akuntansi dan Keuangan, 2007)
Investor protection in highty concentrated ownership as in Indonesia is a crucial problem. Expropriation tends to be high in lower investor protection because controlling shareholders can implement policies that benefit themselves at the expense of outside investors. In a high expropriation, outside investors will choose dividends rather than retained earnings.This paper examines good corporate governance as a solution.for a good investor protection in Indonesia. Using a sample of 245 firms for observdion period of 2001-200j, the results slows that stronger investor ptotection related with lower dividend payout ratio.Kqtwords : Good Corporate Governance, Dividend Payout Ratio,Investor Protection, Concentrated Ownership.